The role of coping strategies in food consumption assessment: evidence from Sudan using FCS and HDDS - Ahmed A. Fadol; Guangji Tong; Muhammad Waqar Akram; Shahla Andleeb; Nida Akram; Khalil Ur Rehman (Cogent Food & Agriculture, 2025)
The measurement of household food consumption in Sudan is highly contentious among researchers and policymakers. This study compares the Food Consumption Score (FCS) and the Household Dietary Diversity Score (HDDS) as tools to assess food insecurity and coping strategies in Sudanese households. Using a cross-sectional dataset of 14,533 households in 18 states, the study evaluates the effectiveness of both indicators in capturing food consumption behaviour. The results show that coping strategies significantly predicted changes in FCS, with a high F-value (24.690) at p < 0.000. In contrast, HDDS, although statistically significant (p < 0.000), showed a weaker relationship (F = 4.644). These results suggest that the FCS is a more robust indicator for assessing food consumption in Sudan. The study emphasises the importance of using a consistent and contextually appropriate measurement approach. It recommends that researchers and policy makers adopt the FCS to better monitor household food insecurity and guide nutrition-related policies and programmes in Sudan.